DEVELOPMENT OF ENGINEERING GEOLOGICAL SECTION OF GEODATABASE OF KYIV - AKSOM, N.; AKSOM, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the article engineer-geological section geodatabase is offered for Kyiv city. It is suggested to organize an engineergeological section as classes/subclasses information and blocks of their treatment. The chart engineer-geological section GDB is developed for Kiev, integration different engineer-geological information in GIS exhaust and tested method and mechanism, the exemplary structure of every layer is created, partly layers and attributive tables are filled.